Estimation of economic and biological properties and productivity of sainfoin collection samples - А. А. Regidin; S. A. Ignatiev; K. N. Goryunov (Зерновое хозяйство России, 2024)
The current paper has presented the estimation results of sainfoin samples developed in the collection nursery of the “ARC “Donskoy”. The purpose of the study was to estimate the main economic and biological properties, feed, and seed productivity of sainfoin collection samples. The objects of study were 25 sainfoin samples of local hybridization. The study was conducted in 2019–2021. Growing and harvesting activities were carried out according to the cultivation technologies recommended for the area of cultivation. The study results of new sainfoin samples developed over several years have shown some patterns in their phenological phases. The studied material includes samples whose time of spring regrowth, beginning of flowering and seed ripening were at the standard level on average over 3 years; these phases of some other samples were longer. The length of economically important periods, from spring regrowth to beginning of flowering and full ripening of sainfoin samples was, respectively, 48–53 days and 91–93 days. The plant height at the beginning of flowering, which has a great influence on sainfoin feed mass productivity, varied from 112 cm to 123 cm. On average, over 3 years, the studied samples were identified by high crude protein percentage in plant mass, varying from 18.12 % to 19.71 %. Samples with 4.4–4.8 kg/m2 had a larger and significantly larger green mass productivity than the standard (3.5 kg/m2). The highest indicators were identified in samples ‘Sin 127’ (186 g/m2), ‘Sin 131’ (170 g/m2), ‘Sin 142’ (184 g/m2), ‘Sin 1.15’ (172 g/m2).